2000
DOI: 10.1038/35017581
|View full text |Cite
|
Sign up to set email alerts
|

Two yeast forkhead genes regulate the cell cycle and pseudohyphal growth

Abstract: There are about 800 genes in Saccharomyces cerevisiae whose transcription is cell-cycle regulated. Some of these form clusters of co-regulated genes. The 'CLB2' cluster contains 33 genes whose transcription peaks early in mitosis, including CLB1, CLB2, SWI5, ACE2, CDC5, CDC20 and other genes important for mitosis. Here we find that the genes in this cluster lose their cell cycle regulation in a mutant that lacks two forkhead transcription factors, Fkh1 and Fkh2. Fkh2 protein is associated with the promoters of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
358
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 297 publications
(376 citation statements)
references
References 26 publications
17
358
0
1
Order By: Relevance
“…We were able to trace this difference to the activity of the yeast forkhead homologues by noting first that the forkhead transcription signature reported by Zhu et al (2000) corresponded with the residual periodic transcription pattern left after MD treatment. This suggests that forkhead-proteinassociated transcription is responsible for driving MDtreated cells through G2 and M. Supporting this hypothesis, we observed that fkh1fkh2 double mutants, when treated with MD, now altered the cell cycle similar to wild-type HP-treated cells.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…We were able to trace this difference to the activity of the yeast forkhead homologues by noting first that the forkhead transcription signature reported by Zhu et al (2000) corresponded with the residual periodic transcription pattern left after MD treatment. This suggests that forkhead-proteinassociated transcription is responsible for driving MDtreated cells through G2 and M. Supporting this hypothesis, we observed that fkh1fkh2 double mutants, when treated with MD, now altered the cell cycle similar to wild-type HP-treated cells.…”
Section: Discussionmentioning
confidence: 97%
“…A full depiction of subclusters, gene Table i. The residual cell cycle clusters that maintained periodic expression under MD (but not HP) treatment included many genes previously associated with regulation by the yeast forkhead homologues Fkh1p and Fkh2p (Zhu et al, 2000); also see Web Supplement Figure iv). The G2/M cluster corresponds to the Clb1 cluster, which is directly regulated by these proteins, whereas the M/G1 and G1 clusters correspond to the Sic1 cluster, which is regulated by a member of the Clb1 cluster, encoding the Swi5p transcription factor.…”
Section: Differential Cell Cycle Transcriptional Effects Of Hp and MDmentioning
confidence: 99%
See 1 more Smart Citation
“…1b). Ndd1 is the activator of the Mcm1-Fkh2 transcription factor complex [21][22][23][24] . The protein levels of Ndd1 oscillate periodically and it has been previously speculated 28 that it might be degraded by the APC/C.…”
Section: Resultsmentioning
confidence: 99%
“…We thus set up an unbiased screen designed to probe the entire yeast proteome. During the pilot stage of this screen, we identified Ndd1, an essential protein, which activates the Mcm1-Fkh2 G2-specific transcription factor [21][22][23][24] . We show here that Ndd1 is an APC/C Cdh1 substrate and that the APC/C Cdh1 is a major regulator of the cell cycle-specific oscillations of Ndd1.…”
mentioning
confidence: 99%